2011
DOI: 10.1117/12.889178
|View full text |Cite
|
Sign up to set email alerts
|

Fat tissue histological study at NIR laser treatment of the skin in vivo

Abstract: Histological slices of skin samples with the subcutaneous adipose tissue after laser irradiation at different doses are analyzed. These data may be used at carrying out of the analysis of histological slices of skin samples with the subcutaneous adipose tissue after photodynamic therapy. The obtained data are important for safe layer-by-layer dosimetry of laser irradiation used in the treatment of obesity and cellulite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Earlier we demonstrated that the combined action of ICG and NIR laser radiation (808 nm) may cause the development of pronounced morphological changes in tissues [33]. It was previously shown that that the dye accumulates in the intercellular space [32,75,76]. In this study, we used ICG dissolved in saline to reduce some negative effect of necrosis on the upper layers of the skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier we demonstrated that the combined action of ICG and NIR laser radiation (808 nm) may cause the development of pronounced morphological changes in tissues [33]. It was previously shown that that the dye accumulates in the intercellular space [32,75,76]. In this study, we used ICG dissolved in saline to reduce some negative effect of necrosis on the upper layers of the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these terms reflects the specificity of biochemical and morphological approaches [30,31]. Depending on technology applied, cell apoptosis or necrosis may take place [32]. Another method of fat tissue destruction, namely photodynamic/photothermal method, may provide reduction of regional or site-specific accumulations of adipose tissue least-invasively [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal fat causes cerebrovascular disease [2]. The laser irradiation method of reducing abdominal fat can thermally decompose fat through the selective irradiation of adipose tissue [3]. The laser has a narrow bandwidth, and the beam is a straight path of light [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, intensive irradiation enables localized thermal decomposition of adipose tissue. However, the intense heat causes side effects, such as trauma, bleeding, burns, and pain [3]. In addition, lasers are expensive and have a high-power consumption.…”
Section: Introductionmentioning
confidence: 99%